FAKTOR DOMINAN PENYEBAB KEHAMILAN RISIKO TINGGI PADA IBU HAMIL DI RUMAH SAKIT ISLAM SAKINAH MOJOKERTO - Kusmindarti, Indah; Kholifah, (JURNAL KEPERAWATAN SEHAT, 2015)
Most of maternal death occurred during pregnancy. High MMR (Maternal Mortality Rate) in Indonesia due to various direct and indirect caused. The main direct caused are hemorrhage, hypertension in pregnancy, and infection. Maternal mortality caused not only directly, by complications of pregnancy and childbirth, but also by various diseases, such as tuberculosis, anemia, malaria and heart disease. The researched objective to determine the dominant factor that caused high-risk pregnancy in pregnant women at Islamic Hospital Sakinah Mojokerto. The study design used descriptive design. The population in this studied that all pregnant women checkups at Islamic Hospital Sakinah Mojokerto as many as 140 pregnant women. Sampling techniques used accidental sampling and obtained as many as 112 high-risk pregnant women samples. Data collected used Rochjati Poedji Score Card. After the data collected then analyzed used percentages. The results shows that the dominant factor cause high-risk pregnancy in pregnant women is unjob pregnant women as many as 67 (59.8%) because most unjob pregnant women is a housewife. Mother not works or housewives who generally have more time, but due to the lack of broader social cause pregnant women to get information about the danger signs of pregnancy. This can lead to high-risk pregnancy in pregnant women. Health professionals need to examine this case to obtain data on the subject . By knows this data , so health workers can provide information and counseling appropriate to the patients condition.Keywords: Causative Factor, Pregnant Women, High-Risk Pregnancy.